Experimental behavior and analysis of high strength concrete beams reinforced with PET waste fiber. (30th May 2020) - Mohammed, Azad A.; Rahim, Aso A. Faqe
Highlights: Properties of high strength concrete (HSC) with PET waste fiber were investigated. Behavior of reinforced concrete beam made of (HSC) with PET fiber was investigated. Existence of PET waste fiber has some effect to enhance the crack control of HSC. Compressive strength loss was observed and to a lesser degree the tensile strength of concrete due to the existence of PET fiber. Cracking performance of the beam was enhanced, but PET fiber has no appreciable effect on the ultimate load capacity. Abstract: This paper describes material properties of high strength concrete containing different PET waste fiber in terms of fiber volume and length. Structural behavior of reinforced concrete beams made of this newly developed concrete has been fairly investigated. Cracking performance of beams was found to improve as a result of using PET waste fiber, but there is no chance to increase the ultimate load capacity. There is some strength loss of the beam mainly attributed to the degradation take place in compressive strength of concrete, but mode of failure of tested concrete beams was almost identical to that of control beam without PET waste fiber. Ultimate moment capacity of concrete section with PET fiber can be calculated accurately following the recommendation of the ACI 318 code. The results are interested and can encourage researchers to work on this kind of recycled high strength concrete for structural applications in future.